Laporan Kasus : Acute Respiratory Distress Syndrome (ARDS) pada Pasien Post COVID-19 dengan Fibrosis - Andry Ganesha Rombe; Wiendo Syahputra Yahya (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
. The Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus (SARS- CoV2) has led to a pandemic situation. According to the WHO classification, COVID-19 patients could be classified with severity as uncomplicated illness, mild pneumonia, severe pneumonia, acute respiratory distress syndrome (ARDS), sepsis and septic shock.Case illustration: A 25 year old female, with a chief complaint of shortness of breath and cough, history of cesarean section surgery with indications of severe preeclampsia and hysterectomy for uterine atony. weeks previously the patient was confirmed positive for COVID-19 without symptoms and tested negative through the Polymerase Chain Reaction (PCR) follow up examination. The Chest X-Ray showed the right lung atelectasis, bronchitis and minimal pleural effusion. CT scan of the chest showed a ground glass opacity in almost all bilateral lung segments with septal thickening in according with the picture of COVID pneumonia with cardiomegaly. The patient was intubated and put on a ventilator due to acute respiratory failure and the drugs include antiviral (oseltamivir), chloroquine, antibiotic (meropenem) and steroid (methylprednisolon) intravenous.Discussion: Post COVID-19 fibrosis is one of the emerging complications of COVID 19 pneumonia and ARDS. This case report highlights ARDS in patient with Pulmonary Post Covid-19 and its challenges in diagnosis and treatment. The combination treatment of mechanical ventilation and drugs such as antiviral,chloroquine, antibiotic, steroid intravenous could give the good outcome for the patient of ARDS due to Pulmonary Fibrosis Post COVID - 19